Building and Testing a Spin Coater for the Deposition of Thin Films on DSSCs - Edwalder Silva Teixeira; Raphael Coelho Cavalcanti; Vanja Fontenele Nunes; Paulo Herbet França Maia Júnior; Francisco Marcone Lima; Diego Caitano Pinho; Men de Sá Moreira de Souza Filho; Ana Fabíola Leite Almeida; Francisco Nivaldo Aguiar Freire (Materials Research, 2021)
Abstract A low cost spin coater was constructed in this work for the deposition of thin films of titanium dioxide (TiO2) on conductive substrate of FTO (fluoride doped tin oxide) with application on dye sensitized solar cells. The results showed a 95% precision between the speed values obtained by the software of C#sharp language and the spin values observed directly on the device. The TiO2 films deposited through the spin coater with different angular speeds were characterized by UV-Vis optical spectrum, scanning electron microscopy (SEM), atomic force microscopy (AFM) and electrical measurements on an active area of 0.25 cm2. The DSSCs assembled with the TiO2 films of double layer deposited by the spin coater had an efficiency value of 12.74%, while the cell with a single layer presented 4.05% efficiency. Therefore, it is concluded that the spin coater assembled in this study at low costs successfully can produce TiO2 electrodes for DSSCs.